Are mental health awareness efforts contributing to the rise in reported mental health problems? A call to test the prevalence inflation hypothesis. (April 2023) - Foulkes, Lucy; Andrews, Jack L.
Abstract: In the past decade, there have been extensive efforts in the Western world to raise public awareness about mental health problems, with the goal of reducing or preventing these symptoms across the population. Despite these efforts, reported rates of mental health problems have increased in these countries over the same period. In this paper, we present the hypothesis that, paradoxically, awareness efforts are contributing to this reported increase in mental health problems. We term this the prevalence inflation hypothesis. First, we argue that mental health awareness efforts are leading to more accurate reporting of previously under-recognised symptoms, a beneficial outcome. Second, and more problematically, we propose that awareness efforts are leading some individuals to interpret and report milder forms of distress as mental health problems. We propose that this then leads some individuals to experience a genuine increase in symptoms, because labelling distress as a mental health problem can affect an individual's self-concept and behaviour in a way that is ultimately self-fulfilling. For example, interpreting low levels of anxiety as symptomatic of an anxiety disorder might lead to behavioural avoidance, which can further exacerbate anxiety symptoms. We propose that the increase in reported symptoms then drives further awareness efforts: the two processes influence each other in a cyclical, intensifying manner. We end by suggesting ways to test this hypothesis and argue that future awareness efforts need to mitigate the issues we present.